2023
DOI: 10.3389/fonc.2023.1089105
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative staging of uterine cancer: can transvaginal ultrasonography play a role?

Abstract: IntroductionPreoperative staging of uterine cancer has recently been implied as an important contribution to an accurate selection of low-risk cases, ultimately avoiding unnecessary lymph node debulking. The aim of this study was to evaluate the validity of transvaginal ultrasonography (TVS) in preoperative staging of uterine cancer in comparison to pelvic magnetic resonance imaging (MRI) and permanent section.MethodsWe conducted a prospective longitudinal multicenter trial between 2017 and 2018. Inclusion cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…As an alternative, a recent study reported the diagnostic performance of a transvaginal ultrasound in evaluating myometrial and cervical stromal invasion [ 21 ]. Diagnostic performance was similar between the ultrasound and MRI in assessing myometrial invasion.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative, a recent study reported the diagnostic performance of a transvaginal ultrasound in evaluating myometrial and cervical stromal invasion [ 21 ]. Diagnostic performance was similar between the ultrasound and MRI in assessing myometrial invasion.…”
Section: Discussionmentioning
confidence: 99%